2012
DOI: 10.1093/jac/dks277
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of antibiotic therapy duration in community- and hospital-acquired bacterial infections

Abstract: Despite the large number of suggestions available in the literature, the optimal duration of antibiotic treatment remains an individual decision mainly based on clinical criteria. Shorter but equally effective regimens would reduce the side effect rates, including both antibiotic resistance and drug expenses. Although several prospective, randomized trials and meta-analyses with the aim of comparing a standard duration with a shorter one for most bacterial infections have been published, to date most current r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 57 publications
0
17
0
2
Order By: Relevance
“…Patients receive specific oral or intravenous antibiotic therapy, or both, targeted toward bacteria isolated during the first-stage surgery [11]. Although the ideal duration for antibiotic therapy is not defined, most of the recent literature recommends a 6-to 12-week course [12][13][14][15]. Once the infection is eradicated, and CRP and ESR levels return to normal, the second surgery is performed to remove the spacer and implant the revision prosthesis.…”
Section: This Article Is Part Of the Topical Collection On Revision Kmentioning
confidence: 99%
“…Patients receive specific oral or intravenous antibiotic therapy, or both, targeted toward bacteria isolated during the first-stage surgery [11]. Although the ideal duration for antibiotic therapy is not defined, most of the recent literature recommends a 6-to 12-week course [12][13][14][15]. Once the infection is eradicated, and CRP and ESR levels return to normal, the second surgery is performed to remove the spacer and implant the revision prosthesis.…”
Section: This Article Is Part Of the Topical Collection On Revision Kmentioning
confidence: 99%
“…Many studies proved the equal efficacy of second and third generation cephalosporins and azithromycin in bacterial eradication with a short course of 3-5 days. 9 Clinical studies and in-vitro models demonstrated longer the course of antibiotics administered, higher are the rates of resistance developed. 9 Misclassifying viral infections as "antibiotic appropriate" scale gives a wrong message on a broader public health perspective.…”
Section: Discussionmentioning
confidence: 99%
“…9 Clinical studies and in-vitro models demonstrated longer the course of antibiotics administered, higher are the rates of resistance developed. 9 Misclassifying viral infections as "antibiotic appropriate" scale gives a wrong message on a broader public health perspective. 10 When a particular antibiotic is prescribed, the susceptible bacteria have less survival advantage than the resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, unnecessarily long therapy could be harmful to patients. In studies of antibiotics used to treat other bacterial infections, it has been suggested that better outcomes occur with shorter rather than longer duration therapy [53]. However, this is a matter of ongoing debate.…”
Section: Discussionmentioning
confidence: 99%